A study on the conformity of four commercially available (sachet packed) dental alginate impression materials to internationally accepted standards as to setting time, packaging and labelling - Gotamco, Cherry Jane L.; Batiller, Gaston M.; Macasaet, Avelino (Adviser).
A disappointing experience with two sachet packed alginate impression materials lead the authors to suspect the existence of trade malpractice among dealers of alginate impression materials. Four commercially available (sachet packet) dental alginate impression materials were chosen. Each brand was then tested for conformity to accepted international standard as to packaging, marking or labelling and setting time. The results reveal that most of the samples tested fall short of international standards. A majority of the brands tested have actual net contents short of that indicated in their labels. The incidence of such practices may be traced to the absence of a body that checks on the quality of these materials. The results are embarrassing and the probability of such irregularities may hold true with other dental materials as well.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental impression materials; Dental materials